La sabiduría desde el “Quaerens intellectum” en Anselmo de Canterbury - Schmidt Andrade, Ciro E. (Sapientia, 2008)
The proof of God’s existence, out of the single idea of God, was and still is a metaphysical experience of which it is possible to say it is perennial. God’s presence in the soul gives life to the formula given by St. Anselm. His analysis aims at bringing to light a presence that remains hidden while being felt. We dwell somewhere between faith and vision. Saint Anselm believes that our understanding in this life is never complete. There are different approaches but the same goal.